A novel ANN-based four-dimensional two-disk hyperchaotic dynamical system, bifurcation analysis, circuit realisation and FPGA-based TRNG implementation. (28th November 2019) - Vaidyanathan, Sundarapandian; Pehlivan, Ihsan; Dolvis, Leutcho Gervais; Jacques, Kengne; Alcin, Murat; Tuna, Murat; Koyuncu, Ismail
This paper describes the modelling, bifurcation analysis, circuit realisation and FPGA implementation of a novel ANN-based four-dimensional two-disk dynamical system exhibiting hyperchaos and hidden attractor. This paper provides a detailed analysis of the multistability, coexisting attractors and bifurcation properties of the novel two-disk dynamical system with hyperchaos. The novel two-disk dynamical system does not possess any rest point pinpointing the presence of hidden hyperchaotic attractor. We realise the dynamic equations of the two-disk hyperchaotic dynamical system with a real circuit. Next, we build design and implementation of ANN-based two-disk hyperchaotic dynamical system on FPGA. Finally, using FPGA-based implementation of the two-disk hyperchaotic dynamical system, we design and implement a novel high-speed True Random Number Generator (TRNG).